QUESTIONS AND PROBLEMS IN CHILD VACCINATION - Florea Iordăchescu (Amaltea Medical Publishing House, 2009)
In the last century, vaccination represented one of the most important accomplishments in biomedical sciences and public health. The lowering incidence of infectious diseases and the rising of life expectancy, due to the diminuation of infectious diseases, related to vaccination, did not make parents and other "specialists" more confident and they keep asking pediatricians and general doctors about the safety of vaccination, about the real possible dangers linked to it. In the article the author presents well documented answers to these questions. The great succes of vaccination resides in solidarity for a a good global cover of at least 90-95% of the population. If the global coverage is less than 90-95%, vulnerable individuals are exposed to infectious diseases and many epidemies may occur.